2020
DOI: 10.1089/dna.2020.5949
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Haplotypes in OPG Gene Are Associated with Premature Coronary Artery Disease and Traditional Cardiovascular Risk Factors in Mexican Population: The GEA Study

Abstract: Basic and clinical research have demonstrated that osteoprotegerin (OPG) plays an important role in the development and progression of cardiovascular diseases. The aim of this study was to evaluate the association of four polymorphic sites (rs2073618, rs3134069, rs3134070, and rs3102735) of OPG gene with premature coronary artery disease (pCAD), and with cardiometabolic parameters. The polymorphisms were genotyped using 5¢ exonuclease TaqMan genotyping assays with real-time PCR in 1098 individuals with pCAD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Nevertheless, the participation of rs3102735 as a susceptibility marker is still under debate. Even if this polymorphism has been shown to be associated with the incidence of diseases other than cardiovascular diseases [ 8 , 28 , 29 ], a lack of association with the incidence of symptomatic CAD [ 30 ] or large artery atherosclerosis stroke [ 28 ] has been reported. The topography of atherosclerotic lesions as well as the stage of the disease may be at the basis of these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the participation of rs3102735 as a susceptibility marker is still under debate. Even if this polymorphism has been shown to be associated with the incidence of diseases other than cardiovascular diseases [ 8 , 28 , 29 ], a lack of association with the incidence of symptomatic CAD [ 30 ] or large artery atherosclerosis stroke [ 28 ] has been reported. The topography of atherosclerotic lesions as well as the stage of the disease may be at the basis of these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased OPG levels cause artery calci cation and atherosclerosis and thus associate with CVD in the general population and in RA patients [10,12,33,34]. However, only speci c variants of the OPG gene have been associated with atherosclerosis and CVD in non-rheumatic patients in few studies [35][36][37].In RA, only two studies have examined the association of different variants of the OPG gene and atherosclerosis and results are somewhat inconsistent. In accordance with our results, Chung et al found that the CC genotype of the rs2073618 was associated with coronary artery calcium, whereas another study failed to associate any of the examined variants with the risk of CV events and designated a possible protective effect of the OPG CGA haplotype on CV risk in the anti-CCP negative RA subset [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The rs2073618 polymorphism of the OPG gene and the A1298C (rs1801131) and C677T(rs1801133)polymorphisms of the MTHFR gene were analyzed by polymerase chain reaction (PCR) of genomic DNA, as previously described [37,98].…”
Section: Osteoprotegerin and Mthfr Genotypingmentioning
confidence: 99%
“…Genome-wide studies (GWAS) and candidate genes have established the participation of various SNPs in the development of CAD [ 13 , 14 , 15 ]. Unfortunately, GWAS studies do not include Mexican populations and candidate gene studies in Mexicans are scarce [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%